2010
DOI: 10.1016/j.nantod.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Emerging links between surface nanotechnology and endocytosis: Impact on nonviral gene delivery

Abstract: Significant effort continues to be exerted toward the improvement of transfection mediated by nonviral vectors. These endeavors are often focused on the design of particulate carriers with properties that encourage efficient accumulation at the membrane surface, particle uptake, and endosomal escape. Despite its demonstrated importance in successful nonviral transfection, relatively little investigation has been done to understand the pressures driving internalized vectors into favorable nondegradative endocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 166 publications
(183 reference statements)
3
148
0
1
Order By: Relevance
“…The combination of liposomes with scaffolds has been already reviewed elsewhere [15,27,108,117]. All these strategies aspire to combine the advantageous properties of liposomes and polymer matrices, aiming at developing materials that can sequester and maintain liposomes at a local tissue site.…”
Section: Combining Liposomes With Scaffoldsmentioning
confidence: 99%
“…The combination of liposomes with scaffolds has been already reviewed elsewhere [15,27,108,117]. All these strategies aspire to combine the advantageous properties of liposomes and polymer matrices, aiming at developing materials that can sequester and maintain liposomes at a local tissue site.…”
Section: Combining Liposomes With Scaffoldsmentioning
confidence: 99%
“…These findings may have significant implications because certain forms of caveolae-mediated endocytosis are thought to avoid the degradative lysosomal compartment. 22 In conclusion, we were able to obtain FN-binding HBc-based VLPs with intracellular targeting properties. Although the potential applications of these NPs in humans may be limited due to possible immunogenicity and the abundance of FN in plasma, the evidence of particles' fast and efficient transmission to target cells opens the possibility for using this system as an intracellular delivery vector in vitro, as well as a model platform for investigation of multifunctional NPs with targeted features.…”
Section: Discussionmentioning
confidence: 77%
“…19 FN acts as a ligand for bacterial and viral adherence to host cells and plays a role in modulating the cellular entry of retroviral vector particles. 20,21 In addition, a number of studies suggested an active role of FN adsorption in cellular uptake of nonviral nanocarriers (for review, see Adler et al 22 A large amount of bacterial FN-binding protein has been identified so far; among them is BBK32, a 47 kDa surfaceexposed lipoprotein and FN-binding adhesin of Borrelia burgdorferi (B. burgdorferi). 23,24 BBK32 contains multiple FN-binding motifs located to an extended intrinsically disordered segment.…”
mentioning
confidence: 99%
“…10,11 At the cell-material interface, the cell-membrane receptor 'integrins' have intricate roles in cell-material adhesion (focal adhesion, or FA), through which regulatory signals are transmitted. FA links the extracellular matrix to induce cytoskeleton contraction.…”
Section: Introductionmentioning
confidence: 99%
“…When modified by 3-aminopropyltriethoxysilane, the material could enhance the transfer of a green fluorescent protein (GFP) reporter gene into human embryonic kidney (HEK) cells using the conventional vectorbased reverse transfection protocol. 17 Because cell behavior and endocytosis are both affected by the integrin-nanotopography interaction, 7,10 we assume that these upright nanosheets may also mediate the endocytosis and transfection of naked plasmid DNA. In this study, we reveal a new method that can be easily scaled up to produce silica upright nanosheets for practical use and a new method to transfer a therapeutic gene into difficult-to-transfect cells (for example, stem cells) using the silica upright nanosheets without any vector.…”
Section: Introductionmentioning
confidence: 99%